Inovasi Model CTL dalam PAI: Kajian Literatur Kritis Terhadap Efektivitas dan Implementasi Nyata - Umam, Khairul (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2025)
This study discusses the contextual learning model in Islamic Religious Education (PAI) that links subject matter with students' real experiences, so that learning becomes more meaningful. The method used is qualitative through literature study with descriptive analysis of journals and books in the last five years. The results of the study indicate that this contextual model emphasizes the strategies of relating, experiencing, applying, cooperating, and transferring, as well as principles such as constructivism, inquiry, asking, learning communities, modeling, reflection, and authentic assessment. The application of the contextual model in PAI has been proven to be able to increase active participation, creativity, and students' understanding of religious values ​​in the context of everyday life. Although it requires high readiness from teachers, the contextual learning model provides contextual, fun, and relevant learning solutions for student development